2006
DOI: 10.1038/sj.bjc.6603109
|View full text |Cite
|
Sign up to set email alerts
|

RET rearrangements in post-Chernobyl papillary thyroid carcinomas with a short latency analysed by interphase FISH

Abstract: Tissue samples from 13 post-Chernobyl childhood thyroid tumours that occurred within a short period of time (4 -8 years) after the Chernobyl accident have been investigated by interphase FISH analysis for rearrangements of RET. In all, 77% of cases showed RET/ PTC rearrangements and a distinct intratumoural genetic heterogeneity. The data were compared to findings on 32 post-Chernobyl PTCs that occurred after a longer period of time (9 -12 years) after the accident. In none of the cases from either group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
4
17
0
Order By: Relevance
“…These findings indicate that the CNAs correlate with the morphological and molecular phenotypes of the investigated cases. The various copy number changes that are present in addition to the RET/PTC rearrangement in RET/PTC positive cases concur with the findings of previous studies reporting that RET/PTC only occurs in a subset of tumor cells and therefore is unlikely to be the only driver of PTCs (12,13,26). Many of the CNAs described in this study have already been described in PTCs from children in one of our previous studies (17) ( Table S5).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings indicate that the CNAs correlate with the morphological and molecular phenotypes of the investigated cases. The various copy number changes that are present in addition to the RET/PTC rearrangement in RET/PTC positive cases concur with the findings of previous studies reporting that RET/PTC only occurs in a subset of tumor cells and therefore is unlikely to be the only driver of PTCs (12,13,26). Many of the CNAs described in this study have already been described in PTCs from children in one of our previous studies (17) ( Table S5).…”
Section: Discussionsupporting
confidence: 80%
“…These findings may therefore reflect more the association between the solid morphological subtype with RET/PTC3 rearrangement and the age of the patient at diagnosis, rather than the etiology of the tumor (5, 10). In addition, the level of RET/PTC expression in PTC has been shown to be highly variable as a result of heterogeneous distribution of RET/PTC within a particular tumor (11)(12)(13)(14). This suggests that rearrangement of the RET oncogene may not be an initiating event and, therefore, the presence of a high frequency of this alteration is not directly linked to radiation exposure.…”
mentioning
confidence: 96%
“…External radiation during childhood increases the risk of thyroid tumors, either benign or malignant (1)(2)(3)(4)8). More than 90% of these cancers are papillary, presenting a RET/ PTC rearrangement in 70% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The translocations of RET and TRK are mostly intrachromosomal, 117 making them relatively difficult to detect by FISH. Studies using FISH to detect RET translocations have found alternating positive and negative areas within morphologically malignant cells of papillary thyroid carcinoma 118 -a finding that may reflect insensitivity of the FISH technique rather than the implausible alternative of multiple independent RET translocations. Polymerase chain reaction-based detection of the translocations is also difficult because the translocations can take place over a large distance.…”
Section: Ancillary Molecular Testsmentioning
confidence: 99%